EFEKTIVITAS METODE HALAQOH DALAM MENINGKATKAN KELANCARAN BACAAN AL-QUR’AN SANTRI - Izharul Haq, Moh. Shobir; Abdurrahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the effectiveness of the halaqoh method in improving the fluency of students' Quran recitation. The halaqoh method is a traditional learning system that emphasizes direct interaction between teachers and students through talaqqi and musyafahah approaches. This study used a qualitative approach with literature study, observation, and interviews. The results showed that emotional closeness between teachers and students, direct correction (tashih), and regular repetition (murojaah) were the main factors in improving reading fluency. Compared to classical methods, halaqoh is more effective because it provides individual attention to students. Therefore, this method remains relevant and worthy of being maintained amidst the development of digital learning.